The relationship between erythrocyte parameters and metabolic syndrome components among patients with Type (2) Diabetes Mellitus - Satmy, Sandy; Remal Asaad, (Latakia University Journal -Medical Sciences Series, 2023)
Many previous studies reported an association between erythrocyte parameters and metabolic syndrome (MS). Due to the high prevalence of MS among patients with Type 2 Diabetes Mellitus (T2DM), our study aimed to examine the relationship between erythrocyte parameters and MS components among patients with T2DM. This current study took place in Tishreen University Hospital and the Diabetes Centre of Lattakia City in Syria. A total of 121 participants who were previously diagnosed with T2DM were included in this study. The results have shown that levels of erythrocyte parameters (RBC, Hb, HCT, and RDW) increased with the number of MS components from 1 to 5. There was a statically significant positive correlation between each of RBC, Hb, and HCT with BP, TG, WC, and BMI and a negative correlation with HDL among males and females. RDW had a positive correlation with BP, WC, and HDL and a negative correlation with TG and BMI in both males and females. In conclusion, high levels of erythrocyte parameters were associated with MS and its components among patients with T2DM. Due to this relationship, it is possible to use these parameters to investigate MS, especially with its high prevalence and dangerous complications.